2022
DOI: 10.3390/gels8110694
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Potato Starch Hydrogel:Glycerol Monostearate Oleogel Ratio on the Physico-Rheological Properties of Bigels

Abstract: Bigel (BG) has been shown to be promising for the food industry due to the possibility to manipulate the properties of the system by adjusting the ratio of each individual phase, namely the hydrogel (H) and oleogel (O) phases. This work aimed to evaluate the influence of the O:H ratio on the physical-rheological properties of BG produced with potato starch (PS) and glycerol monostearate (GM). The hydrogel hardness (i.e., 1423.47 g) directly influenced the viscosity of the BG samples, as BG with a higher H-phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 61 publications
(81 reference statements)
2
12
0
Order By: Relevance
“…For BG at 30:70 and 50:50 ratios the diffraction patterns did not show marked differences, indicating that the amount of OG added in the BG and the phase distribution affect the rearrangement of beeswax crystals. Similar findings have been reported by Alves Barroso et al (2022), who states that the presence of crystalline peaks in BG systems at 2θ close to 20°are due to the main role of OG phases, contributing to form greater crystalline organisation, especially when HG phases do not display defined crystalline peaks.…”
Section: Bigels Characterisationsupporting
confidence: 89%
See 2 more Smart Citations
“…For BG at 30:70 and 50:50 ratios the diffraction patterns did not show marked differences, indicating that the amount of OG added in the BG and the phase distribution affect the rearrangement of beeswax crystals. Similar findings have been reported by Alves Barroso et al (2022), who states that the presence of crystalline peaks in BG systems at 2θ close to 20°are due to the main role of OG phases, contributing to form greater crystalline organisation, especially when HG phases do not display defined crystalline peaks.…”
Section: Bigels Characterisationsupporting
confidence: 89%
“…Similar findings have been reported by Alves Barroso et al . (2022), who states that the presence of crystalline peaks in BG systems at 2 θ close to 20° are due to the main role of OG phases, contributing to form greater crystalline organisation, especially when HG phases do not display defined crystalline peaks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports about the effect of oleogel rate in bigels on the firmness have been done. Alves-Barroso et al (2022) found that an increase of oleogel in bigels diminishes the firmness; however, Zhu et al (2021) found an opposite behavior (i.e., an increase of oleogel in bigel increases the firmness), like the observed behavior in the present work. According to Zhu et al (2021), the firmness is an indication of the strength of intermolecular forces of the gelling network inside the formulations.…”
Section: Texture Analysissupporting
confidence: 78%
“…A frequency sweep was performed in the linear viscoelastic region (LVR) with a frequency of 0.1-100.0 rad/s and a temperature of 25°C. The temperature sweep was carried out 25°C-90°C with 5°C/min and an angular frequency of 10 rad/s at linear viscoelastic region (LVR) (Barroso et al, 2022). This analysis was performed using PP50/S (beeswax and oleogel 1%-10% beeswax) and CP50-1 (RPO and oleogel 0% beeswax) geometries.…”
Section: P R E S S Rheologymentioning
confidence: 99%